INCULCATING CARING AND ENVIRONMENTALLY CULTURED CHARACTERS AMONG MADRASAH IBTIDAIYAH STUDENTS THROUGH THE ADIWIYATA PROGRAM - Fikri, Alfarobi Brillian; Kusumawati, Erna Risfaula; Setya, Makhasin Ariffi (UIN Sunan Kalijaga Yogyakarta, 2022)
The character of caring for the environment needs to be instilled in students from an early age to increase their awareness. This caring is an attitude and action that tries to prevent damage to the surroundings. Therefore, this study aims to describe the formation of caring and environmentally cultured characters in students through the Adiwiyata program at Madrasah Ibtidaiyah Negeri (MIN) 1 Kendal, Central Java, Indonesia. The descriptive qualitative approach was used and the informants were the principal, teachers, and students. Data collection was carried out through observation, interviews, and documentation. Furthermore, data analysis was carried out by reduction, presentation, and verification using source and technique triangulation. The results showed the Adiwiyata program at MIN 1 Kendal generated some character building for students and madrasah residents, such as discipline, cooperation and responsibility, as well as sincerity in charity. The formation of a caring and environmentally cultured character in students through the program is implemented with four essential elements, namely Adiwiyata Madrasah Policies, Curriculum, Participatory-Based Activities, and Support Facilities.